2019
DOI: 10.15252/embr.201847079
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish facial lymphatics develop through sequential addition of venous and non‐venous progenitors

Abstract: Lymphatic vessels are known to be derived from veins; however, recent lineage‐tracing experiments propose that specific lymphatic networks may originate from both venous and non‐venous sources. Despite this, direct evidence of a non‐venous lymphatic progenitor is missing. Here, we show that the zebrafish facial lymphatic network is derived from three distinct progenitor populations that add sequentially to the developing facial lymphatic through a relay‐like mechanism. We show that while two facial lymphatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 59 publications
(143 reference statements)
3
59
0
Order By: Relevance
“…1d, e), suggesting that both proteins have redundant functions during secondary sprouting. Furthermore, we found that both facial lymphatic vessels 18,19 and also the recently discovered lymphatic cell population within the meningeal layer of the zebrafish brain [20][21][22] are completely absent in double mutant embryos (Fig. 1n, o).…”
Section: Resultsmentioning
confidence: 58%
“…1d, e), suggesting that both proteins have redundant functions during secondary sprouting. Furthermore, we found that both facial lymphatic vessels 18,19 and also the recently discovered lymphatic cell population within the meningeal layer of the zebrafish brain [20][21][22] are completely absent in double mutant embryos (Fig. 1n, o).…”
Section: Resultsmentioning
confidence: 58%
“…This indicates a spatially dependent role of Kdr in regulating developmental lymphangiogenesis, providing insight into organotypic modes of lymphatic development that differentially utilize VEGFR2/VEGFR3 signaling. Previous studies have shown that rostral lymphatic progenitors originate from multiple venous and non-venous origins, coalescing to form an integrated craniofacial lymphatic vasculature during zebrafish development (Astin et al, 2014;Eng et al, 2019). Additionally, the distinct signaling pathways required for craniofacial and trunk lymphangiogenesis may indicate that molecularly distinct lymphatic progenitor cells are present in different regions of the embryo as VEGFR2 and VEGFR3 signaling may elicit differential downstream pathways and even transcriptional outcomes (Deng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, late forming angioblasts have been shown to contribute to caudal vasculature between 25 and 29 hpf, after vasculogenesis in the trunk is complete (Fukuhara et al, 2014). In the head, a population of late forming angioblasts have also been found to colonize both lymphatic and arterial vessels (Eng et al, 2019). These studies suggest that apart from LPM and endotome, additional sources of angioblasts may exist to support development of some specific late-forming vessels.…”
Section: Cell Behavior and Regulation Of Vasculogenesismentioning
confidence: 96%